Performance comparison of various denoising filters for brain MRI images - Latha, M; Arun, S (International Journal of Engineering and Technology, 2018)
Communication in the modern age has been done via Visual information which is being transmitted in the form of digital images. The transmitted image often contains noise and need to be preprocessed before applied in algorithms. Image provides some useful structural and functional information about the brain after involving into a simple and non-invasive procedure. Various functional modalities like CT, SPECT and MRI detects some changes in normal metabolism and in flow of blood. If the original image is noisy or has any structural changes, it becomes difficult to identify the required features from the original image and hence preprocessing becomes an essential step. An experimental methodology has been done which compares and classify the various denoising filters.Â Â